Health-illness transition processes in children with complex chronic conditions and their parents: a scoping review - David Loura; Ana Margarida Ferreira; Joana Romeiro; Zaida Charepe (BMC, 2024)
Abstract Background The prevalence of complex chronic conditions (CCC), which cause serious limitations and require specialized care, is increasing. The diagnosis of a CCC is a health-illness transition for children and their parents, representing a long-term change leading to greater vulnerability. Knowing the characteristics of these transitional processes is important for promoting safe transitions in this population. This scoping review aimed to map the available evidence on health-illness transition processes in children with complex chronic conditions and their parents in the context of healthcare. Methods Six databases were searched for studies focusing on children aged 0-21 years with CCC and their parents experiencing health-illness transition processes, particularly concerning adaptation to illness and continuity of care, in the context of healthcare. Studies within this scope carried out between 2013 and 2023 and written in Portuguese or English were identified. The articles were selected using the PRISMA methodology. The data were extracted to an instrument and then presented with a synthesizing approach supporting the interpretation of the results. Results Ninety-eight methodologically broad but predominantly qualitative articles were included in this review. Children with CCC have specific needs associated with complex and dynamic health-illness transitions with a multiple influence in their daily lives. Several facilitating factors (p.e. positive communication and a supportive therapeutic relationship with parents and professionals, as well as involvement in a collaborative approach to care), inhibiting factors (p.e. the complexity of the disease and therapeutic regime, as well as the inefficient organization and coordination of teams) and both positive (p.e. well-being and better quality of life) and negative response patterns (p.e. negative feelings about the chronic illness) were identified. Some interventions to support the transitional process also emerged from the literature. Pediatric palliative care is seen as a good practice and an integrative approach for these children and families. Conclusion Health professionals play a fundamental role in supporting the transitional process and promoting positive response patterns. More significant investment is needed at the clinical and academic levels regarding production and dissemination of knowledge in this area to ensure the awareness of children with CCC and that their needs are fully enhanced. Review registration https://doi.org/10.17605/OSF.IO/QRZC8 .